Detector de raios X baseado no diodo pin - Scarpin, Jorge Alberto (2016)
Ionizing radiation allowed the medical use of diagnostic imaging, whose purpose is to obtain a medical evaluation of tissues and physiological functions of the human body. Its use, however, brought some problems, such as excessive radiation that a person can be exposed. International standards guide on the use of equipment that use radiation, as the doses on patients and occupational workers, and provide recommendations on the use of equipment that produce the X-rays. In recent years, programs have been implemented to guarantee the quality, thus bringing the greatest benefit to those who use ionizing radiation. The purpose of this work is to promote an analysis of the use of a simple circuit capable of detecting the Xrays emitted by a medical diagnostic radiology apparatus. The electrical circuit used contains an X-ray detection system using as transducer a PIN diode. The circuit is simple and inexpensive. Through a fixed X-ray apparatus, multiple exposures were performed with voltage values in kV, current mA and time s that showed the sensor could detect the presence of this radiation for different values set in the apparatus. The circuit was developed based on a diode type PIN sensor, small size element that can be operated at room temperature, and is able to indicate, via the sensor, the interaction of the junction with X-ray photons enabling the detection of the energy of these emitted photons and test the undesirable radiation emitted and radiological accessories.